Implementation Of Hazard Analysis And Critical Control Point At The Marriott Marquis Queen's Park Hotel Kitchen, Bangkok - Pramudia, Heru; Rafi Canon, Muhammad Arsyad (Politeknik Internasional Bali, 2024)
The Marriott Marquis Queen’s Park Bangkok is renowned for the high quality of its services and products, particularly its food. Guests with high expectations naturally anticipate guaranteed food quality. Therefore, the implementation of the Hazard Analysis and Critical Control Points (HACCP) system is crucial in ensuring the safety and quality of the food offered. This study aims to analyze and evaluate the implementation of the HACCP system in the kitchen of the Marriott Marquis Queen’s Park Bangkok to enhance food safety and reduce contamination risks. The research employs a qualitative descriptive method, with data collection through a checklist system designed based on the seven HACCP principles. Based on the conducted analysis, the Hazard Analysis reveals an average score of 4.5 out of 5, with 71% of respondents strongly agreeing, although 29% believe there is room for improvement. The Critical Control Points (CCP) achieved an average score of 4.6; however, 43% of respondents feel that enhancements are necessary. The Critical Limits have an average score of 4.5 and are expected to undergo periodic updates. Furthermore, the monitoring of CCP garnered an average score of 4.5, indicating the importance of consistent oversight. For Corrective Actions, the average score of 4.4 reflects that 64% of respondents strongly agree, but 36% emphasize the need for improvements in documentation. In terms of Verification Procedures, the average score is 4.4, with 50% of respondents strongly agreeing, highlighting the necessity for greater objectivity in the verification process. Lastly, in Documentation and Record Keeping, the average score of 4.5 indicates that 43% of respondents strongly agree; however, record-keeping needs to be more organized and easily accessible.